Effect Of Ethephon Doses On Vegetative Characters, Sex Expression and Yield Of Cucumber (Cucumis sativus cv. Bhaktapur Local) In Resunga Municipality, Gulmi, Nepal - Dhakal, Shiva; Karki, Mahesh; Subedi, Pritee; GC, Aarati (International Journal of Applied Sciences and Biotechnology, 2019)
A study on the effect of ethephon doses on vegetative characters, sex expression and yield of cucumber (Cucumis sativus cv. Bhaktapur Local) was conducted in Gulmi, Nepal during 21st April to 24th August 2017. The experiment was laid in single factor Randomized complete Block Design (RCBD) with 4 replication and 5 treatments. Four different doses of ethephon 100, 200, 300 & 400 ppm with control were applied. Two sprays of ethephon was made one at two true leaf stage and other at four true leaf stage. Ethephon was found to reduce the plant height compared to control, minimum (238.8 cm) with 400 ppm and maximum (310.4 cm) with the control. The number of nodes and branches per plant were found to be highest with 300 ppm. Ethephon was found to shift first male flowers and female flowers towards upper and lower nodes respectively. The plot treated with 300 ppm ethephon, bearing 20.31 female flowers per plant was found superior to other doses for increasing total female flowers. Maximum and minimum number of male flowers per plant was recorded with control(107 per plant) and 400 ppm (46.90 per plant) respectively. Similarly, 300 ppm of ethephon was found superior for reducing (male: female) sex ratio. Maximum yield 27.51 t/ha was recorded with 300 ppm and minimum yield of 17.48 t/ha with the control. 57% increment in the yield was observed with 300 ppm ethephon as compared to the control. Thus, proper use of ethephon is found to be beneficial to farmers. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 370-377